Biocontrol Strategies Using Streptomyces spp. and Trichoderma spp. against the Sugarcane Smut Pathogen Sporisorium scitamineum: An in Vitro Study - Indrawan, Arga Dwi; Raharjo, Laksamana Agadhia; Rahmadhini, Noni (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
Sporisorium scitamineum is a Basidiomycota pathogen that causes smut disease in sugarcane plants. The pathogen can infect all types of sugarcane, with the extent of damage depending on the plant's susceptibility. Farmers rely on chemical pesticides to control S. scitamineum , but these pesticides have negative environmental impacts. Using Trichoderma sp. and Streptomyces sp. as biocontrol has been proven against fungal infections and is safe for the environment. This study evaluated the potential of Trichoderma sp. and Streptomyces sp. against S. scitamineum under in vitro conditions. Each of the three isolates of Trichoderma sp. and Streptomyces sp. was assessed using the VOC (Volatile Organic Compound), chitinase enzyme, and in vitro antagonistic assays. The results indicated that Streptomyces spp. demonstrated higher chitinase activity compared to Trichoderma spp., with isolate ST1 having the highest chitinase index at 3.7%. VOC test demonstrated that Streptomyces spp. markedly inhibited the mycelial growth of S. scitamineum, attaining inhibition rates of up to 82%. Conversely, Trichoderma spp. exhibited enhanced antagonistic activity via direct interaction, with isolate TD2 suppressing pathogen growth by 82% in dual-culture assays. The findings show that Streptomyces spp. and Trichoderma spp. suppressed S. scitamineum in different but complementary ways. The study shows that they could be used as environmentally friendly biological control agents to manage sugarcane smut.